Internet censorship detected in Algeria (Algeria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Algeria. Data sourced from CensoredPlanet.
Censorship Incident ID: DZ-2026-0023. Severity: critical. Confidence: 65%